2022
DOI: 10.3389/fpls.2021.787292
|View full text |Cite
|
Sign up to set email alerts
|

Approaches Involved in the Vegetable Crops Salt Stress Tolerance Improvement: Present Status and Way Ahead

Abstract: Salt stress is one of the most important abiotic stresses as it persists throughout the plant life cycle. The productivity of crops is prominently affected by soil salinization due to faulty agricultural practices, increasing human activities, and natural processes. Approximately 10% of the total land area (950 Mha) and 50% of the total irrigated area (230 Mha) in the world are under salt stress. As a consequence, an annual loss of 12 billion US$ is estimated because of reduction in agriculture production infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 200 publications
1
45
0
Order By: Relevance
“…Induction of ROS under stress conditions is correlated with electrolyte leakage and membrane damage [ 58 ]. Our results showed similarity with findings of [ 41 , 59 , 60 ] who reported less reduction in MSI in salt-tolerant genotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Induction of ROS under stress conditions is correlated with electrolyte leakage and membrane damage [ 58 ]. Our results showed similarity with findings of [ 41 , 59 , 60 ] who reported less reduction in MSI in salt-tolerant genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…The selected tolerant and sensitive genotypes were re-evaluated in a further study to identify the biochemical, physiological, and ionic mechanisms of salinity tolerance. The better performance of salt-tolerant genotypes under stress conditions was found to be associated with maintenance of high K + /Na + ratio, photosynthetic activity, accumulation of osmotic regulators, and higher activities of antioxidant enzymes that minimize the production of ROS [ 39 , 40 , 41 ]. The results of these studies were found consistent with our experimental findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, carotenoids are proved to respond to salt stress [30,31]. Carrots are among the vegetable crops that have a very low salinity threshold [32] and are rich in carotenoids, but the specific salt response mechanism is not clear so far. Hence, it is necessary to investigate the dynamic changes and mechanisms of carotenoids under salt stress in carrots.…”
Section: Introductionmentioning
confidence: 99%
“…Saline soils and saline irrigations constitute a serious production problem for vegetable crops as saline conditions are known to suppress plant growth [13].The present study demonstrates salinity adversely affected the growth of tomato cv Marmande regardless of SA treatments. Earlier studies have shown that the concentration of 100 mM NaCl decreased total dry biomass and leaf area [11,14].…”
Section: Discussionmentioning
confidence: 51%